Pathways in theology: ecumenical, African and Reformed - Naudé, Piet (Beyers Naudé Centre series on public theology, 2015)
Part 1. Essays in ecumenical theology.Accept one another : an introduction to "reception" as ecumenical concept --Regaining our ritual coherence : the question of textuality and worship in ecumenical reception --Doxology and praxis : the ecumenical significance of religious experience in South Africa of the 1990s --Confessing Nicea today? : critical questions from a South African perspective --Identity and ecumenicity : how do we deal theologically with so-called "non-theological" factors? --The Belhar struggle in ecumenical perspective --Belhar : for South Africa, North America and worldwide --Edmund Schlink (1903-1984) : telling his story from a South African perspective --Part 2. Essays in African, liberation and feminist theologies.Theology with a new voice? : the case for an oral theology in the South African context --Toward a local Zionist theology : the role of the outsider theologian --Jesus as manga? : christological enrichment from a Zionist perspective --The "pregnant Christ" : a feminist reinterpretation : the role of women in the 1990s --Can our creeds speak a gendered truth? : a feminist reading of the Nicene Creed and the Belhar Confession --Liberation theology as orthopractical theology : a methodological evaluation --The poor as hermeneutical subjects in liberation theology --Preaching from the Old Testament : a perspective from Liberation Theology --Part 3. Essays in Reformed theology.Is there a future for scholarship? : Reformed theological scholarship in a transforming higher education environment --The limitations of problem solving as a criterion for paradigms in theology : in dialogue with Wentzel van Huyssteen --The two faces of Calvin in South Africa : in honour of the 500th commemoration of John Calvin's birth --A letter from John Calvin to South African Christians, 500 years on --The reception of Karl Barth in South Africa 1960-1990 : selected perspectives --The marks of the church in South Africa today : in dialogue with Jürgen Moltmann on his 80th birthday --"Public theology" from within the church? : a reflection on aspects of the theology of W.D. Jonker (1929-2006) --The Belhar Confession (1982/1986) and Church and society (1986) : a comparative essay in five statements --The Dutch Reformed Church's role in the context of transition in South Africa --Constructing a coherent theological discourse : the main challenge facing the Dutch Reformed Church in SA.